THE EFFECT OF WORK-LIFE BALANCE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH MENTAL HEALTH AS AN INTERVENING VARIABLE AN AUDIO EQUIPMENT MANUFACTURING - Purwanti; Rismawati (Majapahit Journal of Islamic Finance and Management, 2026)
This research examines the impact of workplace equilibrium and physical-social conditions on employee productivity mediated by psychological well-being in PT. EMSONIC INDONESIA Audio Company Indonesia's Unit Department, addressing performance variability from extended hours and inadequate support amid rising mental health issues in Indonesia. A quantitative approach employed saturated sampling of 113 employees, with primary data from 5-point Likert questionnaires via Google Forms, analyzed via PLS-SEM in SmartPLS 4.0.9.9, including measurement model evaluation (outer loadings, AVE, HTMT), structural assessment, bootstrapping (5,000 resamples), and validity-reliability checks. Findings reveal workplace equilibrium (β=0.327, p=0.007) and organizational environment (β=0.467, p<0.001) significantly enhance psychological well-being and productivity (direct effects: β=0.354/0.288, p<0.05), with indirect mediation (β=0.104/0.148, p<0.05) and strong predictive power (R²=0.733; AVE>0.5, α>0.87). The core synthesis supports Social Exchange Theory in manufacturing contexts. Policy implications urge firms to promote work-life balance through flexible hours, improved lighting, and support to safeguard mental health and boost productivity. Originality stems from the first PLS-SEM analysis using full population data from an Indonesian audio firm, resolving prior conflicting findings and highlighting mediation in non-shift overtime settings.